Delayed Severe Airway Obstruction Due to Hematoma Following Stellate Ganglion Block. Issue 5 (September 1998) - Mishio, Mutsuo; Matsumoto, Tsutomu; Okuda, Yasuhisa; Kitajima, Toshimitsu
Abstract : Background and Objectives: Delayed onset of airway obstruction following stellate ganglion block (SGB) may be life threatening. We treated a patient who developed a severe airway obstruction caused by a large hematoma several hours after an SGB. Methods: A 62-year-old woman suffering from sudden deafness developed dyspnea 2 hours after undergoing her fourth SGB, and evidenced swelling and tenderness in her anterior neck and chest. Her pharyngolaryngeal tissues were edematous, and the glottis was markedly narrowed. Computed tomograms and magnetic resonance images revealed a large soft tissue mass extending from the first cervical vertebra to the diaphragm. Results: Surgical tracheotomy was performed to maintain her airway. Swelling of the vocal cord disappeared on the eleventh day after the operation. Conclusions: We believe that the SGB needle injured the vertebral artery and caused massive hemorrhage anterior to the cervical vertebra, subsequently inducing pharyngolaryngeal edema by obstructing the venous and lymphatic drainage of the cervical region.